Morphological Character of The Natural Orchid Phalaenopsis Spp. Results of Colchicine Polyploidy Induction - Sri Hartati; Samanhudi Samanhudi; Endang Suprapti (Pusat Penelitian dan Pengembangan Bioteknologi dan Biodiversitas (P3BB) LPPM UNS, 2024)
Induction of polyploidy in orchids can cause morphological changes such as larger leaf and flower sizes, longer bloom durations, and sharper flower colors. Morphological characterization needs to be done to determine the morphological changes that occur after colchicine treatment. This study aims to determine the morphological characters of natural orchids Phalaenopsis spp. polyploidy induction using colchicine. The research was carried out from November 2021-February 2022 at the Screen House, Faculty of Agriculture, UNS. The plant materials used included P. violacea from Sulawesi, P. violacea from Java, and P. Ambilis from Ambon. The treatment used was colchicine 1,250 ppm which was applied to flower buds using the cotton method with 2 replications. The collected data were analyzed by descriptive analysis and paired T-test using IBM SPSS Statistics 26 to compare the average performance of mutant plants with control plants. Induction of polyploidy using colchicine with a concentration of 1,250 ppm could increase the size of leaves, flower stalks, flowers, dorsal and lateral sepals, and petals in P. violacea from Java, P. violacea from Sulawesi, and P. amabilis from Ambon.